Cardiovascular Risk Reduction in High-Risk Pediatric Patients: A Scientific Statement From the American Heart Association. Issue 13 (26th March 2019) - de Ferranti, Sarah D.; Steinberger, Julia; Ameduri, Rebecca; Baker, Annette; Gooding, Holly; Kelly, Aaron S.; Mietus-Snyder, Michele; Mitsnefes, Mark M.; Peterson, Amy L.; St-Pierre, Julie; Urbina, Elaine M.; Zachariah, Justin P.; et al.
Abstract : This scientific statement presents considerations for clinical management regarding the assessment and risk reduction of select pediatric populations at high risk for premature cardiovascular disease, including acquired arteriosclerosis or atherosclerosis. For each topic, the evidence for accelerated acquired coronary artery disease and stroke in childhood and adolescence and the evidence for benefit of interventions in youth will be reviewed. Children and adolescents may be at higher risk for cardiovascular disease because of significant atherosclerotic or arteriosclerotic risk factors, high-risk conditions that promote atherosclerosis, or coronary artery or other cardiac or vascular abnormalities that make the individual more vulnerable to the adverse effects of traditional cardiovascular risk factors. Existing scientific statements and guidelines will be referenced when applicable, and suggestions for risk identification and reduction specific to each setting will be described. This statement is directed toward pediatric cardiologists, primary care providers, and subspecialists who provide clinical care for these young patients. The focus will be on management and justification for management, minimizing information on pathophysiology and epidemiology.